ANALISIS PROFITABILITAS BANK SEBAGAI TREN PERTUMBUHAN TRANSAKSI DI INDONESIA - Sayyidatul Aisyah Abigail Alhabi Chandra (2022)
This paper aims to determine the profitability condition of Digital Banks in Indonesia, especially Jenius, Bank Jago and Blu BCA, against the growth trend of their transactions. Profitability is a calculation to measure the company's ability to make a profit. The method used in conducting this analysis is to collect data from the financial statements for the first quarter to the fourth quarter of the 2021 period. The financial statements in question are in the form of income statements and balance sheets, then transaction volumes by looking at the number of users (customers) from annual reports and news. There are four profitability guidance formulas used, namely Return on Assets (ROA), Return on Equity (ROE), Operating Expenses to Operating Income (BOPO), and Net Interest Margin (NIM). The results of the data processing were tested with a ratio standard based on SEOJK.03/2019 concerning the Bank Health Level Assessment System, Financial Services Authority Regulation Number 14/ SEOJK.03.2017, and the Financial Statement Analysis book tahhun 2008. The results of the analysis of the three Digital Banks showed that Jenius, which has a better performance From the level of increase in transaction volume, Digital Bank customer users experienced a positive increase in each quarter.